HERPETOFAUNA DI HUTAN DATARAN RENDAH HAYA, MAMBERAMO, PAPUA - Keliopas Krey (FMIPA Universitas Papua, 2008)
During about 19 days field work survey (7-25 February 2008) on the Haya lowland forest area, Mamberamo Papua. Eksploration is the methods used in this study. Reptiles and amphibians were collected by hand on the night and day in several type of habitat (plains, swamp, oxbowlake, stream, creeks and hills). The result showed that 48 species of herpetofauna (21 species frogs, 19 species of lizard, six species of snakes and one species of turtles and crocodile) were found.